The effect of sprint interval training with short repetitions on hippocampal Brain-derived neurotrophic factor levels, learning and spatial memory in adult Wistar rats - Maryam Afshani; Esmail Nasiri; Mohsen Khalili (Fiyz̤, 2023)
Background: Different intensities of exercise may have a different effect on the level of brain-derived neurogenic factor (BDNF). Hence, this study aimed to determine the effect of sprint interval training with short repetitions on hippocampal BDNF level, spatial learning and memory in adult rats. Materials and Methods: Sixteen Wistar rats were randomly divided into the control (CO, n=8) and exercise (EX, n=8) groups. The exercise was performed for 8 weeks, 3 sessions per week, 4-9 repetitions of 10 seconds sprints, and 1-minute rest. At the end of the training period, the learning and memory of the animals were evaluated by Y maze and shuttle box tests. 48 hours after the test, the rats were anesthetized and the hippocampal tissue was isolated. BDNF levels were measured in hippocampal tissue homogeneity. The independent t-test was used to analyze the data at the alpha level of 0.05. Results: Statistical analysis of the data showed that the level of BDNF in EX hippocampus was significantly higher than that of CO (P<0.001); While there was no significant difference between the two groups in terms of the results of Y-maze and shuttle box behavioral tests (P˃0.05). Conclusion: According to the findings of the present study, it seems that SIT may help to increase the hippocampus BDNF level in rats by spending much less training time (30-40 min./week) than other training protocols; But it has no positive or negative effect on learning and memory.